Self-Determined Learning, Digital Competence, and Learning Styles as Predictors of Students' Attitudes toward Flipped Learning - Muhammad Haristo Rahman; Amiruddin; Nurlaela (Indonesian Technology and Education Journal, 2026)
Flipped learning effectiveness depends heavily on student attitudinal acceptance, yet prior research has typically examined its determinants in isolation focusing separately on technology acceptance, self-regulation, or learning preferences. This study proposes and tests an integrated structural model linking Self-Determined Learning (SDL), Digital Competence (DC), and Learning Style (LS) to students' attitudes toward flipped learning (SFLIPP) among undergraduates in Indonesian higher education. A cross-sectional survey was administered to 395 students, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS SEM). The measurement model demonstrated robust reliability and validity (AVE > .50; CR > .838; HTMT < .90). Results showed that Learning Style was the strongest direct predictor of attitudes (β = .413, p < .001), followed by Digital Competence (β = .190, p < .001) and Self-Determined Learning (β = .164, p < .001). SDL exerted a substantial total effect on SFLIPP (β = .535), with approximately 69.3% of this effect mediated indirectly predominantly through LS (71.4% of the mediated portion) rather than DC (28.6%). The model explained 42.7% of the variance in attitudes. These findings indicate that fostering positive attitudes toward flipped learning requires a holistic approach that simultaneously strengthens student agency, cultivates responsible digital competence, and ensures pedagogical preference alignme.